Mathematical model for the process of benzene alkylation by higher olefins - Fetisova V. A.; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Kravtsov A. V. Anatoly Vasilyevich (2010, 2010)
Title screen